The Universal Church of the Kingdom of God in Australia: Local Congregants and a Global Spiritual Network - Openshaw, Kathleen (Journal for the academic study of religion, 2019)
The Brazilian megachurch, the Universal Church of the Kingdom of God (UCKG), has a global network of branches. Its Australian headquarters is a dynamic spiritual space where ideas, people, material culture and spirits are exchanged from across the globe. This article follows the journey of a single vial of oil to illustrate the global flows that take place through the UCKG Australia. With each stop the vial accrues spiritual capital before its final destination. Drawing on two years of ethnographic research, I argue that the UCKG's global networks allow congregants access to, and enables them to pass on, spiritual capital thus providing personal agency to overcome life difficulties via supernatural means. Through this vial's journey, I will show how global religious practices are locally lived and highlight the local spiritual significance of globally mobile religious material culture.